Are Reduced Levels of Coagulation Proteins Upon Admission Linked to COVID-19 Severity and Mortality? - Ceballos, Francisco C.; Ryan, Pablo; Blancas, Rafael; Martin-Vicente, María; Vidal-Alcántara, Erick Joan; Peréz-García, Felipe; Bartolomé, Sofía; Churruca-Sarasqueta, Juan; Virseda-Berdices, Ana; Martínez-González, Oscar; Brochado-Kith, Oscar; Rava, Marta; et al. (Frontiers in Medicine, 2021)
Background: the link between coagulation system disorders and COVID-19 has not yet been fully elucidated. Aim: evaluating the association of non-previously reported coagulation proteins with COVID-19 severity and mortality. Design: cross-sectional study of 134 COVID-19 patients at admission and classified according to the highest severity reached for COVID-19 (severe, moderate or asymptomatic/mild) and 16 healthy control individuals). Methods: coagulation proteins levels (antithrombin, prothrombin, factor_XI, factor_XII, and factor_XIII) were measured in plasma by ProcartaPlex Panel (Invitrogen) multiplex immunoassay, upon diagnosis. Results: we found higher levels of antithrombin, prothrombin, factor XI, factor XII and factor XIII in asymptomatic/mild and moderate COVID-19 patients than healthy individuals. Interestingly, decreased levels of antithrombin, factor XI, XII and XIII were observed in those patients who eventually developed severe illness. Additionally, survival models showed us that patients with lower levels of these coagulation proteins had an increased risk of death. Conclusion: COVID-19 provokes early increments of some specific coagulation proteins in most patients. However, lower levels of these proteins at diagnosis might “paradoxically” imply a higher risk of progression to severe disease and COVID-19-related mortality.